PENENTUAN JENIS PUPUK TERHADAP TANAMAN KACANG TANAH MENGGUNAKAN METODE FORWARD CHAINING - Arie Rafika Dewi (JURNAL AKADEMIKA)
Expert systems (expert systems) is a software package or a package of computer programs shown as a provider of advice and aids in solving problems in certain specialist fields such as science, engineering, mathematics, medicine, education and so forth. This research aims to devise an expert system application to determine the type of fertilizer suitable for growing peanuts can assist the Department of Agricultu re Asahan district to provide counseling to farmers with forward chaining method. The design of this application is made to the programming language Visual Basic 6.0 and Microsoft Access 2010. Through this application, users can consult with the appropriate system to consult with an expert to find out what fertilizer suitable for the type of land owned by the user